HUBUNGAN ANTARA FREKUENSI BERMAIN GAME ONLINE DENGAN KEDISIPLINAN BELAJAR - Fitriatul Masruroh; Ellyana Ilsan Eka Putri (Jurnal Ilmiah Ar-Risalah: Media Ke-Islaman, Pendidikan dan Hukum Islam, 2021)
This study aims to examine the relationship between the frequency of playing online games with student learning discipline. The hypothesis proposed is that there is a negative relationship between the frequency of playing online games with student learning discipline. The population of this study were students taken using the Purposive Random Sampling technique, namely students covering eight existing faculties, namely the Faculty of Psychology, Faculty of Teacher Training and Education, Faculty of Law, Faculty of Social and Political Sciences, Faculty of Engineering, Faculty of Islamic Religion, Faculty of Economics, Faculty of Agriculture, who are actively playing games. on line. The independent variable in this study is the Frequency of Playing Online Game Clash Of Clans (COC) which is expressed by a scale, while the dependent variable is learning discipline which is also expressed by a scale. Data analysis used Product Moment Correlation analysis. The results of the analysis showed that rx = 0.223 with p = 0.071, (p > 0.05), this means that there is no significant relationship between the frequency of playing the online game Clash Of Clans (COC) and Student Learning Discipline. These results indicate that the hypothesis proposed in this study is rejected.